1803. Clinical Impact of Rapid Blood Culture Diagnostics Differs by Time of Day and Gram Stain Type: Lessons From Implementation of Verigene® Blood Culture Testing in a Children's Hospital. (26th November 2018) - Katz, Sophie; Banerjee, Ritu; Schmitz, Jonathon; Gillon, Jessica
Abstract: Background: Rapid blood culture diagnostics paired with antimicrobial stewardship (AS) enhances appropriate antimicrobial treatment for bloodstream infections (BSI). Ideal implementation strategies for blood culture diagnostics are not clear, including whether to perform molecular testing during off-hours or for all organism types. Methods: To determine whether the clinical impact of the Verigene® Blood Culture Nucleic Acid Tests (VG) is influenced by time of day and Gram-positive (GP) or Gram-negative (GN) organism, we performed a single-center, retrospective evaluation of children with BSIs and VG testing April 2017–March 2018. VG testing was performed on all Gram stain positive blood cultures 24/7. AS providers were notified of VG results at all hours, but AS interventions occurred on weekdays, during office hours. Wilcoxon rank-sum and chi-squared tests were used for analyses. Results: Two hundred fifty-seven isolates (GP:184, 72%; GN:73, 28%) were identified from 224 cultures by standard of care (SOC) conventional culture. VG and SOC results were concordant in 173/224 (77%) cultures overall, 168/197 (85%) monomicrobial cultures, and 5/27 (19%) polymicrobial cultures. Thirty-eight of 257 isolates (15%) were not targets on VG. Among on-panel organisms, discordance was similar for GN (4/48, 8.3%) and GP isolates (16/171, 9.4%). Among 95 opportunities for antibiotic optimization based on VG results, antibiotic changes occurred in 80 (84%), with 48 de-escalations, 11 escalations, and 21 averted antibiotic starts. More modifications were made for patients with GP vs. GN BSI (75 vs. 5, P < 0.001). For GP BSI, mean time from VG result to antibiotic modification was 8.92 hours overall, and faster during day shift than night shift, although not statistically significant ( P = 0.49) (Figure 1). Among patients with GP BSI, 4 were not admitted and 21 had antibiotics discontinued within 24 hours. Conclusion: At our children's hospital, VG testing implemented with AS resulted in antibiotic optimization, but not as promptly as expected. Antibiotic changes occurred more frequently for GP than GN BSI and occurred more quickly when VG testing occurred during the day vs. night. There is a need for strategies that improve the impact of rapid blood culture diagnostics, especially during off-hours and for GN BSI. Disclosures: R. Banerjee, Accelerate Diagnostics, Biomerieux, BioFire: Grant Investigator, Research grant and Research support. J. Schmitz, Luminex: Grant Investigator, Research grant.